2023
DOI: 10.3390/ma16114177
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Shear Behavior of Non-Stirrup Ultra-High Performance Concrete Beams

Abstract: Due to the high tensile strength of ultra-high performance concrete (UHPC), the shear stirrups in UHPC beams could potentially be removed. The aim of this study is to assess the shear performance of non-stirrup UHPC beams. Six UHPC beams were tested and compared with three stirrup-reinforced normal concrete (NC) beams, taking into consideration the testing parameters of steel fiber volume content and shear span-to-depth ratio. The findings demonstrated that incorporating steel fibers can efficiently strengthen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The test results confirmed the role of steel fibers in improving the shear resistance of non-stirrup UHPC beams. This finding is in accordance with the experimental results of Li et al [50], although the ductility coefficients of the UHPC beams in this study were lower than those of the aforementioned study. This discrepancy may be attributed to the differing shear span-to-effective depth and reinforcement ratio between this study and that of Li et al [50].…”
Section: Effect Of Steel Fibers On Failure Modes and Crack Patternssupporting
confidence: 93%
See 2 more Smart Citations
“…The test results confirmed the role of steel fibers in improving the shear resistance of non-stirrup UHPC beams. This finding is in accordance with the experimental results of Li et al [50], although the ductility coefficients of the UHPC beams in this study were lower than those of the aforementioned study. This discrepancy may be attributed to the differing shear span-to-effective depth and reinforcement ratio between this study and that of Li et al [50].…”
Section: Effect Of Steel Fibers On Failure Modes and Crack Patternssupporting
confidence: 93%
“…For the French standard formulae, the ratio V u1 /V u,test ranged from 0.51 to 1.44, with a mean of 0.91, an STDEV of 0.33, and a coefficient of variation of 0.36. Comparison with Li et al's [50] experimental findings suggested that the formulae were more accurate for UHPC beams with larger shear span-depth ratios. In addition, the average ratio of the calculated shear capacity to the tested shear capacity for the French standard formulae was closest to 1.00.…”
Section: Comparison Of Calculated Valuesmentioning
confidence: 69%
See 1 more Smart Citation
“…In order to obtain a comprehensive assessment of the seismic behavior of reinforced concrete structures, this study specifically focuses on the effect of two different types of stirrups, i.e., hooked and unhooked stirrups. Previous research has shown that hooked stirrups can improve energy dissipation and ductility by providing additional restraint to the concrete core, while unhooked stirrups, although widely used, may provide relatively limited benefits in this regard [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Rosso et al [19] estimated the effect of corrosion on the capacity and ductility in their study.…”
Section: Introductionmentioning
confidence: 99%